“da niuna cura accompagnato fuori che quella di scoprire antiche cose”.: Nuovi dati sugli scavi Campanari a Vulci (Rapporti di scavo inediti, 09.11.1835–28.05.1836) - Franceschini, Mariachiara; Pasieka, Paul P. (Römische Mitteilungen, 2021)
Hitherto unpublished reports of the excavations by the Società Vincenzo Campanari – Governo Pontificio at Vulci found at the German Archaeological Institute in Rome provide an important contribution to the better understanding of the early excavations at Vulci, their temporal and spatial progress, the dissemination of the finds, and the mechanisms of the art market in the late 1830s. The reports – signed by Domenico Campanari and addressed to Karl Josias von Bunsen – span the entire second excavation season between November 9th 1835 and May 28th 1836 both on the plateau of the Etrusco-Roman city and in the necropolis. We have been able to identify a group of 37 objects in various European and non-European museums and collections and connect them with the excavations of the Campanaris in Vulci. It was thus possible outline the lively network of antiquarians, scholars and collectors within which the Campanaris operated and for whom scientific and commercial interests appeared complementary.